2017
DOI: 10.2109/jcersj2.17051
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared luminescence from double-perovskite Sr<sub>3</sub>Sn<sub>2</sub>O<sub>7</sub>:Nd<sup>3+</sup>: A new class of probe for in vivo imaging in the second optical window of biological tissue

Abstract: Inorganic phosphors that emit near-infrared (NIR) light are highly valued as fluorescent probes for in vivo imaging of biological tissue. NIR-imaging, however, is limited by the paucity of probes that emit over the NIR-II window (10001400 nm). We are interested in exploring the potential of double-layered perovskite structures harboring lanthanide ions as NIR-II fluorescent probes. In this report, we describe the synthesis, and characterization of the photoluminescence, afterglow and thermoluminescence of Nd 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…[100] T -and [010] T -axes (α ≠ β). 49 The phase transition Pccn→Bmab at 420 K in Sr 2 SnO 4 structure is well consistent with the neutron diffraction studies carried by Fu et al 13 However, the second phase transition Bmab→I4/mmm may occur at lower temperature of 480-500 K, comparing with Fu et al results at 573 K. Such inaccuracy may be a result of large gap between two measured temperature points (473-573 K).…”
Section: -supporting
confidence: 87%
“…[100] T -and [010] T -axes (α ≠ β). 49 The phase transition Pccn→Bmab at 420 K in Sr 2 SnO 4 structure is well consistent with the neutron diffraction studies carried by Fu et al 13 However, the second phase transition Bmab→I4/mmm may occur at lower temperature of 480-500 K, comparing with Fu et al results at 573 K. Such inaccuracy may be a result of large gap between two measured temperature points (473-573 K).…”
Section: -supporting
confidence: 87%
“…When Nd 3+ content is 0.2 mol%, ML emission spectrum first appears, which consists of two emission bands of 700‐850 nm and 850‐1000 nm. The 850‐1000 nm emission band comes from the transition ( 4 F 3/2 → 4 I 9/2 ) of Nd 3+ ions, and the host Sr 3 Sn 2 O 7 is responsible for the 700‐800 nm emission band, since the blank sample shows similar photo‐emission as Figures illustrates. When the Nd 3+ content increases to 0.5 mol%, the ML intensity of host begins to decrease.…”
Section: Resultsmentioning
confidence: 77%
“…Moreover, it has been shown that the NIR ML of Nd 3+ -doped materials include line emissions in the second optical window of biological tissue (NIR2, as shown in Fig. 67) [124,125,368,369]. The ability to generate NIR light from ML materials using ultrasound excitation [23,102,174,326], coupled with the greater transmission of NIR photons through living tissue could lead to exciting developments in medicine, including high-contrast in vivo imaging of tumors and other diseased states.…”
Section: Nir-ml Imagingmentioning
confidence: 99%